2000
DOI: 10.1103/physreve.62.6409
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous chaos in coupled map lattices with small-world interactions

Abstract: In certain physical situations, extensive interactions arise naturally in systems. We consider one such situation, namely, small-world couplings. We show that, for a fixed fraction of nonlocal couplings, synchronous chaos is always a stable attractor in the thermodynamic limit. We point out that randomness helps synchronization. We also show that there is a size dependent bifurcation in the collective behavior in such systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
109
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(110 citation statements)
references
References 16 publications
0
109
0
1
Order By: Relevance
“…Among those, automata epidemics simulations [13] and Web-browsing studies [14] have revealed the importance of shortcuts. Numerical work on synchronization of Kuramoto oscillators [3], discrete maps [15] and Hodgkin-Huxley neurons [16] has shown improved SW synchronizability, as intuitively expected. However, these numerical examples are not generic, and fail to provide insight into how the SW property influences the dynamics.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Among those, automata epidemics simulations [13] and Web-browsing studies [14] have revealed the importance of shortcuts. Numerical work on synchronization of Kuramoto oscillators [3], discrete maps [15] and Hodgkin-Huxley neurons [16] has shown improved SW synchronizability, as intuitively expected. However, these numerical examples are not generic, and fail to provide insight into how the SW property influences the dynamics.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Bishop & Atmanspacher [2004]). For this reason, several authors have directed their attention to the analysis of the stability in CMLs (e.g., Mackey & Milton [1995], Belykh et al [2000], Gade & Hu [2000], Gelover-Santiago et al As a common feature of the (so far) few studies of asynchronous updating, it has been reported that it facilitates the synchronization and stabilization of CMLs decisively. In particular, Mehta & Sinha [2000] demonstrated that the dynamics at individual lattice cells is strongly synchronized by coupling among cells.…”
Section: Stabilizationmentioning
confidence: 99%
“…Lots of existing work on synchronization are conducted on chaos (e.g. Gade & Hu (2000)), coupled maps (e.g. Jalan & Amritkar (2003)), scale-free or small-world networks (e.g.…”
Section: Decentralized Synchronization With Adaptive Controlmentioning
confidence: 99%